Estimation of macular pigment optical density in the elderly: Test–retest variability and effect of optical blur in pseudophakic subjects - Gallaher, Kevin T. (2007)
The reproducibility of macular pigment optical density (MPOD) estimates in the elderly was assessed in 40 subjects (age: 79.1 ± 3.5). Test–retest variability was good (Pearson’s r coefficient: 0.734), with an average coefficient of variation (CV) of 18.4% and an intraclass correlation coefficient (ICC) of 0.96. The effect of optical blur on MPOD estimates was investigated in 22 elderly pseudophakic subjects (age: 79.9 ± 3.6) by comparing the baseline MPOD, obtained with an optimal correction, with MPODs obtained with a ±1.00-diopter optical blur. This optical blur did not cause differences in the MPOD estimates, its accuracy, or test duration.